Incubator humidity and temperature control in infants born at 22–23 weeks' gestation - Kurimoto, Tomonori; Ibara, Satoshi; Ishihara, Chie; Naito, Yoshiki; Hirakawa, Eiji; Yamamoto, Tsuyoshi (Early Human Development, 2022)
Preterm infants, especially those born at ≤23 gestational weeks (GW), present with extremes in insensible water loss (IWL) and changes in water balance. To prevent water loss from the skin and achieve skin maturation without infection, we investigated transepidermal water loss (TEWL), IWL from the skin (IWL-s), and electrolyte balance with differences in high incubator humidity and temperature control from birth to postnatal 1 month in 22–23 GW and 24–25 GW infants. Prospective cohort study. Extremely preterm infants born at 22–23 GW (n = 11) and 24–25 GW (n = 11), admitted to the neonatal intensive care unit between September 2018 and October 2019. Total fluid intake (TFI), fluid output volume, TEWL, IWL-s, and electrolyte balance were compared between the two groups with controlled incubator humidity and temperature, gradually decreasing the humidity and ambient temperature from 95% to 50% and from 37.0 to 34.0 °C, respectively, while maintaining the central body temperature at 36.5–37.5 °C. TEWL and IWL-s between the 22–23 and 24–25 GW was not significantly different for infants at postnatal age. No significant difference in electrolyte imbalance was noted between the two groups, within the first 7 days. Differences in TEWL and IWL-s were eliminated with corresponding humidity and temperature adjustments. Incubator humidity and temperature control should aid management of 22–23 GW infants to reduce IWL, facilitate skin maturation, and prevent infection. •Optimized incubator settings eliminate water loss differences between 22 and 23- and 24–25-week gestation.•Elimination of water loss occurs despite differences in skin maturation levels.•Optimized incubator settings improve outcomes of extremely preterm neonates.